2022
DOI: 10.21037/apm-22-555
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy, safety, and medication compliance of roxadustat on peritoneal dialysis patients with renal anemia affected by the COVID-19 pandemic: a retrospective study

Abstract: Background: Current studies have limited data on long-term treatment safety and medication compliance of roxadustat for renal anemia in peritoneal dialysis (PD) patients. We aimed to analyze the long-term efficacy, safety, and medication compliance of roxadustat in the treatment of renal anemia in patients with PD who discontinued recombinant human erythropoietin (rhEPO) treatment due to the corona virus disease 2019 (COVID-19) outbreak.Methods: We retrospectively collected patients who were switched from rhEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…21 Bao et al switched treatment with rhEPO to treatment with roxadustat for patients undergoing PD and found that their Hb levels increased by an average of 20.7 g/L compared with those before treatment; furthermore, their serum ferritin levels decreased at the beginning of treatment. 22 During this study, both groups experienced increased ferritin levels during infection, with a more significant increase observed in the roxadustat group. However, the recovery of ferritin levels after infection occurred faster in the roxadustat group, possibly because of hepcidin regulation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…21 Bao et al switched treatment with rhEPO to treatment with roxadustat for patients undergoing PD and found that their Hb levels increased by an average of 20.7 g/L compared with those before treatment; furthermore, their serum ferritin levels decreased at the beginning of treatment. 22 During this study, both groups experienced increased ferritin levels during infection, with a more significant increase observed in the roxadustat group. However, the recovery of ferritin levels after infection occurred faster in the roxadustat group, possibly because of hepcidin regulation.…”
Section: Discussionmentioning
confidence: 57%
“…Akizawa et al found that serum hepcidin levels decreased in patients undergoing PD who were treated with roxadustat, indicating an increase in iron absorption and utilization 21 . Bao et al switched treatment with rhEPO to treatment with roxadustat for patients undergoing PD and found that their Hb levels increased by an average of 20.7 g/L compared with those before treatment; furthermore, their serum ferritin levels decreased at the beginning of treatment 22 . During this study, both groups experienced increased ferritin levels during infection, with a more significant increase observed in the roxadustat group.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis showed that the cognitive impairment group had lower compliance in all 4 dimensions compared to the normal cognition group (Table 3). There are many factors that can affect compliance, including age, diabetes history, residual kidney function, serum albumin, and high peritoneal transport status, [18][19][20] but there is relatively little research on the role of cognitive dysfunction in compliance. The results of this study showed that cognitive dysfunction may be an important factor in the low compliance of CAPD patients, indicating that targeted interventions for CAPD patients with cognitive dysfunction to improve compliance and prognosis are necessary.…”
Section: Discussionmentioning
confidence: 99%